Prevalence of prehypertension and its associated factors among adults attending outpatient clinic in Universiti Sains Malaysia Hospital - Rafan, Siti Nurhani (2017)
Background: Prehypertension is a new term introduced by The Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation and Treatment of High Blood Pressure (JNC-7). Prehypertension is defined as blood pressure from 120 to 139 mmHg systolic or 80 to 89 mmHg diastolic. Estimation of prevalence of prehypertension in population and identify cardiovascular associated factors is important to reduce the progression to hypertension. Objectives: To determine the prevalence of prehypertension and associated factors among adult attending outpatient clinic in USM Hospital. Methodology: A cross sectional study was conducted in 2015 among adults attending outpatient clinic in USM Hospital. A total 151 adults age 18-year-old and above participated in this study. Face to face interview was done by using Malay and English version of Malaysia NCD (Non-communicable Disease) surveillance questionnaire, which consist of sociodemographic, lifestyle status and measurement of anthropometric data. Blood pressure was measured three times using sphygmomanometer and the first reading was removed and average from two reading was recorded for further data analysis. Logistic regression was done to look at the associated factors of prehypertension.Result: The prevalence of prehypertension was 37.1% (95% CI: 29.29, 44.69). Factors associated with prehypertension in this study were age (OR:1.06; 95% CI: 1.02,1.11; p=0.007), male (OR:4.44 ;95% CI: 1.58, 12.44; p=0.005) and abnormal waist circumference (OR:31.65; 95% CI: 11.25,89.02; p<0.001) from multiple logistic regression analysis. Conclusion: The prevalence of prehypertension among adult attending outpatient clinic was 37.1% and it was comparable with other studies in Malaysia. Increasing age, male gender and abnormal waist circumference were associated with prehypertension. An awareness of prehypertension among healthcare providers and education of prehypertension among community need to be implemented to increase awareness regarding the risk of getting hypertension and cardiovascular diseases.